OPTIMALISASI KEWENANGAN AMICUS CURIAE KOMNAS HAM DALAM PROSES PEMERIKSAAN PERKARA DI PENGADILAN BERDIMENSI HAK ASASI MANUSIA - Wahyuni, Ridha; Wananti, Atik (UNES Law Review, 2022)
Komnas HAM as a state institution have authorized by law to provide amicus curiae for legal settlement of public cases with a human rights dimension. Until now, Komnas HAM has carried out this authority, but in practice there are still various obstacles, both external and internal, so that its implementation has not been optimal.This study using a juridical-normative research method, with an analytical-descriptive approach to see how the law works in practice. There is a difference in the views of the judges on the position of the amicus curiae of Komnas HAM which is considered the same as the opinion of the Experts, while the Amicus Curiae is more of an institutional opinion and can be submitted individually, therefore it is necessary to issue SEMA so that there is a common view and understanding for judges in seeing this authority, Second ; UU no. No. 39/1999 on Human Rights has not clearly and firmly regulated the authority of Komnas HAM's amicus curiae, making it difficult for Komnas HAM to draft technical regulations for its implementation.